Spellbinding sentences : a writer's guide to achieving excellence & captivating readers - Baig, Barbara, frey50 (Cincinnati, Ohio Writer's Digest Books, 2015)
Elevate Your Writing From So-So To Spectacular! Great writing requires more than an original idea, compelling characters, or a scintillating plot. An author needs all of these to be successful, but writing--and writing well--also demands an entirely different skill set. Spellbinding Sentences arms you with the tools you need to master the power of the English language. In this book, you'll learn the different qualities of words and the many ways those words can be combined to create sentences that hook readers. You'll emulate sentences from your favorite writers, practice proven techniques
Title Page; Copyright Page; Epigraph; Welcome; Section 1: The Mastery Path; Chapter 1: Mastering the Craft; Mastering a Writer's Skills; What You Need to Master Sentence Craft; Chapter 2: Claiming Your Power: Learning Through Practice; What Is Practice?; Chapter 3: The Basic Sentence Craft Practices; Basic Practice #1: Waking Up the Word Mind; Basic Practice #2: Keeping a Notebook; Basic Practice #3: Reading as a Writer; Basic Practice #4: Reflecting on Your Practice; Make Practice Part of Your Life; Section 2: The Power of Diction: Choosing Words; Chapter 4: The Word Hoard;The Benefits of Unpacking Your Word HoardBuild Your Word Hoard; Training Your Word Mind; Take Time to Reflect; Chapter 5: Making Meaning; What Do We Mean by "Meaning"?; Time to Reflect; Chapter 6: The Qualities of Words; The Qualities of Words 1: Formal/Informal; The Qualities of Words 2: General/Specific; The Qualities of Words 3: Abstract/Concrete; Take Time to Reflect; Chapter 7: The Language of the Imagination; Images: The Language of the Imagination; The Vocabulary of the Senses; Balancing Showing and Telling; Take Time to Reflect; Looking Ahead. Section 3: The Power of Function: What Words DoChapter 8: Parts of Speech; Parts of Speech 1: Content Parts of Speech; Parts of Speech 2: Structural Words; Take Time to Reflect; Chapter 9: Making Phrases; What Is a Phrase?; Composing with Phrases; The Power of Phrases; Take Time to Reflect; Section 4: The Power of Syntax: Ordering Words; Chapter 10: Making Spells: The Magic of Sentences; Kinds of Sentences; Sentence Kernels; Syntactic Slots; Take Time to Reflect; Chapter 11: Elaborating the Basic Sentence; Elaborating the Basic Sentence Patterns; Take Time to Reflect. Chapter 12: Extending the Basic SentenceExtending the Basic Sentence 1: Adding Together Independent Clauses; Extending the Basic Sentence 2: Adding Dependent Clauses; New Sentence Structures; Take Time to Reflect; Section 5: The Power of Composition: Putting it All Together; Chapter 13: Making Sentences Move; A Command of Syntactic Structures; Options for Composition; Take Time to Reflect; Chapter 14: Writing in Rhythm; The Music of Language; Take Time to Reflect; Section 6: Using Your Power; Chapter 15: Power and Responsibility; The Dance of Writing; The Journey Towards Mastery. Practicing in the WorkThe Benefits of The Mastery Path; From Play to Deliberate Practice; Moving On; For Further Reading; Acknowledgments
Keywords: Writing; Report writing; Handbooks and manuals